2018
DOI: 10.1038/s41375-018-0089-x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in lower-risk MDS patients compared with age- and sex-matched reference populations: a European LeukemiaNet study

Abstract: In myelodysplastic syndromes (MDS), health-related quality of life (HRQoL) represents a relevant patient-reported outcome, which is essential in individualized therapy planning. Prospective data on HRQoL in lower-risk MDS remain rare. We assessed HRQOL by EQ-5D questionnaire at initial diagnosis in 1690 consecutive IPSS-Low/Int-1 MDS patients from the European LeukemiaNet Registry. Impairments were compared with age- and sex-matched EuroQol Group norms. A significant proportion of MDS patients reported moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 34 publications
1
92
0
Order By: Relevance
“…Red cell transfusion dependency is associated with decreased overall and leukaemia‐free survival in MDS, independent of cytogenetic risk groups and with a reduced QoL (Jadersten et al , ; Malcovati et al , ; de Swart et al , ). The European MDS (EUMDS) Registry programme has also demonstrated inferior QoL and decreased health utility in transfusion‐dependent compared with transfusion‐independent patients (Stauder et al , ). Although haemoglobin concentration is reported to have the greatest impact on QoL in MDS patient (Stauder et al , ), optimal transfusion support in MDS has not been established and it remains unclear whether different red cell transfusion policies would modify clinical outcomes, QoL and functional measures.…”
mentioning
confidence: 99%
“…Red cell transfusion dependency is associated with decreased overall and leukaemia‐free survival in MDS, independent of cytogenetic risk groups and with a reduced QoL (Jadersten et al , ; Malcovati et al , ; de Swart et al , ). The European MDS (EUMDS) Registry programme has also demonstrated inferior QoL and decreased health utility in transfusion‐dependent compared with transfusion‐independent patients (Stauder et al , ). Although haemoglobin concentration is reported to have the greatest impact on QoL in MDS patient (Stauder et al , ), optimal transfusion support in MDS has not been established and it remains unclear whether different red cell transfusion policies would modify clinical outcomes, QoL and functional measures.…”
mentioning
confidence: 99%
“…Our center initiated an MDS registry, now with national participation, that has been conducting prospective assessments of MDS patients every 4 to 6 months using these quality‐of‐life instruments. This registry and others have shown that transfusion dependence and lower hemoglobin level are consistent independent predictors of inferior quality of life as measured by global health status, fatigue, and self‐rated utility . In one analysis, a hemoglobin level of 10 g/dL or greater was the key threshold at which many function and symptom scores plateaued .…”
mentioning
confidence: 81%
“…22 Both MDS and AML patients experience a significant symptom burden and restrictions in their HRQOL, which can negatively influence their clinical outcomes. 5,15 Furthermore, their self-reported experience could even provide a reliable prediction for overall survival. 23 Therefore, it is crucial to find the most suitable PROMs that have been validated for use in these patient populations.…”
Section: What Is (Or Could Be) the Specific Clinical Relevance Of Youmentioning
confidence: 99%
“…3 Patients with MDS often present with symptoms related to low blood counts such as fatigue, paler skin, frequent infections, bleeding, and bruising. 4,5 However, fatigue and impaired health-related quality of life (HRQOL) can only be partially explained by anemia and may also be caused by molecular aberrations, hyperinflammation, and dyspnea. [6][7][8][9] AML is a heterogeneous blood cancer, most commonly associated with bone marrow dysfunction and the production of high numbers of immature myeloid cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation